Determining factors of poverty line in East Java by using log-normal and log-gamma regression - Erdkhadifa, Rendra (Indonesian Journal of Islamic Economics Research, 2025)
This study reviews the factors that have an impact on the poverty line in East Java. Poverty analysis is essential as it reflects regional welfare and economic conditions and guides policy design, given its systemic impact on other sectors. In addition, policies in poverty alleviation can reduce social disparities and economic development. This study uses a sample consisting of regencies and cities in East Java in 2023. A quantitative approach is applied in research with an associative research type. Data analysis technique used in the study is to apply log-normal regression and log-gamma regression Referred to the results of the analysis carried out, the right model to represent the poverty line is log-gamma regression. With alpha 5%, the predictor variables that significantly affect positive are the education level, and open unemployment rate. Total population has negative effect the poverty line significantly. Another result shows that economic grows doesn’t affect significantly to the poverty line. The results suggest that education, unemployment, and population are key determinants of the poverty line in East Java, highlighting the importance of comprehensive policies aimed at enhancing educational outcomes, expanding employment prospects, and ensuring inclusive development instead of depending exclusively on economic growth